Association with fertility, marriage and birth - Mumbai Archive Project Team (Jio Institute, 2024)
Holika is associated with fertility, marriage, and birth; hence, she is treated like a new bride. Accordingly, all the rituals that are performed for the bride during a Koli wedding are also performed for Holika.